DESIGN AND BUILD THE SLIDING DRUM COLLECTOR WITH RPM COUNTER ARDUINO FOR NANOFIBER FABRICATION - Nugroho, Panji Setyo; Ariyanto, Dewa Pascal; Widayani, Della Astri; Hikamiah, Luluk Arifatul; Amaratirta, Jasmine Cupid; Harjunowibowo, Dewanto; Rezeki, Yulianto Agung (Instrumentasi, 2024)
The rotational speed of the drum collector is an important parameter to determine the morphology of the nanofiber. Currently, many researchers are modifying single nozzle into multi-nozzle to obtain a wide range of materials. However, it requires more powerful syringe-pumps or increasing their number, leading to escalated cost. In addressing this issue, the sliding drum collector with an RPM counter is proposed as a solution. This apparatus uses a DC motor 775 and a stepper motor Nema17 as the driving device and an IR-sensor as the RPM counter. The RPM counter on this apparatus has also been calibrated and obtained an accuracy value of 97.87% and a precision value of 96.45%. The performance of the sliding drum collector has been validated. The sliding drum collectors have been proven to produce wider material with an area of (389 Â± 8) cm2, (66 Â± 18) cm2 larger than an ordinary drum collector.